Food transgressions making sense of contemporary food politics - Goodman, Michael K. 1969-; Sage, Colin (Critical food studies, 2014)
Reconnecting so-called alternative food geographies back to the mainstream food system - especially in light of the discursive and material 'transgressions' currently happening between alternative and conventional food networks, this volume critically interrogates and evaluates what stands for 'food politics' in these spaces of transgression now and in the near future and addresses questions such as: What constitutes 'alternative' food politics specifically and food politics more generally when organic and other 'quality' foods have become mainstreamed? What has been the contribution so far of an 'alternative food movement' and its potential to leverage further progressive change and/or make further inroads into conventional systems? What are the empirical and theoretical bases for understanding the established and growing 'transgressions' between conventional and alternative food networks? Offering a better understanding of the evolving position of the corporate food system vis a vis alternative food networks, this book considers the prospects for economic, social, cultural and material transformations led by an increasingly powerful and legitimated alternative food network.